Improving Islamic Education Learning Outcomes Through the Cooperative Model of Teams Games Tournament Type at SMP Negeri 1 Sei Bamban - Nasution, Ade Syahrani; Andriani, Novita; Purba, Doni Ariandi (Program Studi Pendidikan Profesi Guru Fakultas Tarbiyah dan Keguruan UIN Ar-Raniry Banda Aceh, 2024)
This study aims to improve student learning outcomes in Islamic religious education learning by using the Cooperative Model Type Teams Games Tournament. This study is a classroom action research that uses four steps, namely planning, action, observation and reflection. The subjects of this study were junior high school students. The data for this study were obtained by test and observation techniques. Tests are used to measure learning outcomes and observations are used to analyze teacher and student learning activities. The data analysis technique used in this study is descriptive statistics by comparing the results obtained with indicators of research success. The results of the study indicate that the Cooperative Model Type Teams Games Tournament can improve student learning outcomes in Islamic religious education learning. This can be seen from the increase in the percentage of student learning completion in each cycle with details of the pre-cycle 40.19%, the first cycle 51.87% and in the second cycle increased to 81.32%. Thus, the use of video can be used as an alternative to improve student learning outcomes in Islamic religious education learning.